CHARACTER EDUCATION MANAGEMENT AT DOKTOR NUGROHO UNIVERSITY MAGETAN AND INSTITUTO POLITECNICO DE BETANO TIMOR LESTE - Abdul Gafur; Ida Wahyu Wijayati; Eka Jefri Aldi Yuliasmono (CV. Radja Publika, 2022)
Abstract This study aims to analyze the management of character education at Universitas Doktor Nugroho Magetan and Instituto Politécnico de Betano Timor Leste, focusing on policies, implementation practices, challenges, student perceptions, and recommendations to improve its effectiveness. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with university leaders, lecturers, and students, participant observation, and documentation of character education policies and programs at both universities. Data analysis was carried out thematically with an inductive approach to explore the main themes related to character education management. The results of the study show that both universities have implemented a structured character education policy, although with different approaches. Universitas Doktor Nugroho Magetan integrates character education into the academic curriculum through ethics and morals courses, while Instituto Politécnico de Betano focuses more on developing social character and leadership through extracurricular activities and community service. The practice of implementing character education is running well in both universities, although there are differences in its implementation. The main challenges faced are limited resources, difficulties in aligning perceptions about the importance of character education, and less active student involvement. Nevertheless, most students have a positive perception of the character education they receive.